Efektifitas Penerapan Metode Demonstrasi Video Visual Dalam Kemampuan Siswa Pada Materi Praktik Ibadah Shalat - Mutakin; Mufti Ali; Hunainah; Wasehudin (Mu'allim, 2025)
ABSTRACT The purpose of this paper is to explain the reasons why the visual video demonstration technique works very well in teaching students the ability to practice prayer. This article discusses how to incorporate prayer into daily routines and provides a theoretical background on how to use t-test or anova to measure students' abilities in a visual video demonstration-based evaluation. An attempt to characterize the characteristics of students' abilities in prayer practice was carried out using the visual video demonstration approach. The True Experimental Pretest-Posttest Control Group Design was used in this study. This design involves randomly selecting two groups and administering a pretest to determine the initial conditions of each group. If there is no statistically significant difference between the experimental and control groups on the pretest, then the findings are satisfactory. The theoretical purpose of this experimental approach is to ascertain, by using the visual video demonstration technique (X), its effectiveness in improving students' abilities in the material of prayer practice (Y).